Genetic variants IL1B +3954C>T and -511C>T associated with incapacity and allodynia in migraine - Silva, Aline Vitali da; Khouri, Barbara Ferreira; Rezende , Debora Villas Boas; Pezzini , Ana Paula Gallina; Espinosa, Beatriz Rabello; Ahrens , Tainah Mendes; Antonucci , Adriano Torres; Bello , Valéria Aparecida; Frederico, Regina Célia Poli; Coral , Carlos Eduardo; Reiche , Edna Maria Vissoci; Simão , Andrea Name Colado (Headache Medicine, 2022)
Introduction The main mechanisms in the physiopathology of migraine are cortical spreading depression and trigeminal activation with the release of CGRP. Neurogenic inflammation and neuroinflammation can exert an influence over both these mechanisms, but there are still a number of gaps in our understanding. Interleukin (IL)- 1β is a pro-inflammatory cytokine whose levels of plasma increase during the attack phase of migraine. Thus far, its genetic variants have not been well studied. Objective To investigate the association between the genetic variants IL1B +3954C>T (rs1143634) and -511C>T (rs16944) and susceptibility to migraine and its clinical characteristics. Subjects and Methods Case control study comprising 307 participants, of whom 152 had a diagnosis of migraine and 155 were healthy controls, paired by sex, age, ethnicity and BMI. The clinical and demographic data were evaluated. The patients with migraine were interviewed using a structured form containing information about the type of migraine (with or without aura, episodic or chronic), age at onset of the disease, frequency of attacks, accompanying symptoms that triggered headaches. The patients also answered validated questionnaires to evaluate incapacity (Migraine Disability Assessment - MIDAS) and impact (Headache Impact Test - HIT-6) for migraine, the presence of allodynia (ASC-12), as well as symptoms of anxiety (State Anxiety Inventory - STAI 1 and 2), depression (Beck Depression Inventory) and a hyperacusis scale. The genetic variants IL1B +3954C>T (rs1143634) and -511C>T (rs16944) were identified using polymerase chain reaction (PCR) and the fluorescence levels of PCR products were evaluated using a Step One thermocycler (Applied Biosystems). The analyses were conducted using the dominant, codominant, recessive and over- dominant genetic models. Categorical data were evaluated via the chi-squared test or Fisher’s exact test, and continuous data were evaluated using the Mann-Whitney test. (To see the complete abstract, please, check out the PDF).